2022
DOI: 10.1021/acsomega.2c05318
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Anti-inflammatory Effects of Bacopa-Derived Bioactive Compounds Using Network Pharmacology andIn VitroStudies

Abstract: Bacopa monnieri is reported as a potent Indian medicinal plant that possesses numerous pharmacological activities due to the presence of various bioactive compounds. These pharmacological activities were used in the ancient medicine system to cure inflammatory conditions. Bacopa has the ability to reduce acute pain and inflammation by inhibiting the enzyme cyclo-oxygenase-2 (COX-2) and reducing COX-2-arbitrated prostanoid mediators. Moreover, the anti-inflammatory property may also be associated with the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…This study also hypothesizes that the potential phytocompounds identified from BM can be employed to regulate signaling pathways associated with target genes, which could lead to treating inflammation-responsive diseases. As expected, the results obtained in vitro revealed that the identified potential phytocompound effectively inhibits the gene expression responsible for inflammation, such as COX2 and iNOS, in LPS-induced RAW264.7 cells [133].…”
Section: Bm and Inflammationsupporting
confidence: 82%
See 1 more Smart Citation
“…This study also hypothesizes that the potential phytocompounds identified from BM can be employed to regulate signaling pathways associated with target genes, which could lead to treating inflammation-responsive diseases. As expected, the results obtained in vitro revealed that the identified potential phytocompound effectively inhibits the gene expression responsible for inflammation, such as COX2 and iNOS, in LPS-induced RAW264.7 cells [133].…”
Section: Bm and Inflammationsupporting
confidence: 82%
“…A pilot study showed that BM phytocompounds such as quercetin can exhibit a relevant anti-inflammatory action. The results showed the interaction with inducible Nitric Oxide synthase (iNOS), Cyclooxygenase-2 (COX-2), Lipoxygenase (LOX), C-C chemokine receptor type 1 (CCR1), MMP9, and signal transducers and activators of transcription (STAT3) genes [133]. Constantini et al [134] evaluated the anti-inflammatory effects of BM extract in neuroinflammation in vitro model (neuronal SH-SY5Y cells that underwent stimulation with Interferon-γ (INF-γ) and TNF-α regarding toxicity, cell viability, and cytokine gene expression.…”
Section: Bm and Inflammationmentioning
confidence: 99%
“…Bacopa monnieri extract (BME) contains saponins such as bacosides, avonoids, bacosaponines, bacopaside N1 etc. [24][25].BME hasan anti-in ammatory, anti-apoptotic, antioxidative and memory-boosting role in many neurological diseases [26][27][28]. In the light of its nootropic effect, the present study has been designed to study the effects of Bacopa monnieri extract (CDRI-08) on AMPA receptor subunit; GluR1 and GluR2, its tra cking proteins and regulatory molecules(CREB and BDNF) in the hippocampus of rotenone-induced PD mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Bacopa monnieri is a key ingredient in many Ayurvedic herbal preparations and is used in Indian medicine as a nootropic to enhance cognition and memory and also utilises to treat various diseases and disorders (Nemetchek et al, 2017). In this study, we utilized, B. monnieri bioactive compound known as stigmasterol-enriched extract (STIG) has long been utilised in Indian herbal therapy to treat numerous diseases and ailments, such as diabetes, depression, CVD, inflammation, and others (Ibrahim et al, 2022;Jeyasri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…There is still a lack of information regarding how specific active components of B. monnieri interact with biological proteins, genes, and cells. Therefore, it is necessary to conduct an association analysis of Bacopa monneiri's biological characteristics with respect to probable targets and their possible mechanisms (Jeyasri et al, 2022;Rajan et al, 2015). Network pharmacology, which integrates systems medicine analysis with biomedical big data, has recently become an interesting new area of drug development.…”
Section: Introductionmentioning
confidence: 99%